(3OdGFd GdNjQGJ hThGQb GdCfhGQ aj PcQ GdUdGI Ydi GdfHj GdeNJGQs - (3GdLRhdj, eMeO Hf SdjeGf Hf YHO GdQMef, J(B870(3g`s
(3ChdgG (B:s
(3bGd CHh YHO Gddg eMeO Hf SdjeGf GdLRhdj GdMeO ddg GdPj gOGfG ddEjeGfhHYO gPG aGdZQV aj gPG GdcJGH PcQ GdUdGI Ydi GdfHjhSejJg HcJGH OdGFd GdNjQGJs
(3BNQgG (B:s
(3dG Edg EdG CfJ HLGg SjOfG eMeO NGJe GdfHjjf hEeGe GdeQSdjf hYdi Bdg hUMHg CLeYjfs
(3aj Chdg ahGFO hCOYjI hUdhGJ ef b(B1 - (3b(B5s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 151s
(3eYLe GdeDdajf(B: 3 / 333s
(3cTa GdXfhf(B: 1 / 759s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs